Use of traction screw to aid in fracture reduction in bilateral parasymphysis fracture of mandible. Issue 3 (24th September 2015) - Jaisani, Mehul R; Pradhan, Leeza; Dongol, Ashok; Acharaya, Pradeep; Sagtani, Alok
Abstract: Treatment of bilateral parasymphysis fracture often requires special attention due to airway considerations and difficulty in achieving precise anatomic reduction. The central fracture fragment is often displaced posteriorly and inferiorly due to muscle pull, and this adds to difficulty in reduction and stabilization of the central fracture fragment during plate fixation. With this article, we advocate a technique using stainless steel screw and self‐holding screwdriver to manipulate the central fragment and achieve an anatomic reduction. We have used this technique in 12 patients with bilateral parasymphysis fracture without any complications and have found it very effective.